2012
DOI: 10.3343/alm.2012.32.6.392
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Pseudoreticulocytosis in Leukocytosis Samples Using the Sysmex XE-2100 Analyzer Depends on the Type and Number of White Blood Cells

Abstract: BackgroundThe reticulocyte count is a good marker of erythropoietic activity of the bone marrow. In the mid-1990s, automated flow cytometric analysis replaced microscopy for the quantification of reticulocytes. Leukocytosis cases with an erroneously high reticulocyte count and a high immature reticulocyte fraction (IRF) have been reported. In this study, we analyzed reticulocyte counts in leukocytosis samples, in an effort to identify a correction method.MethodsThe study comprised of 21 samples from 16 leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Other causes for discrepancies between automated and manual reticulocyte analyses include the presence of giant platelets, platelet clumps, abnormal WBC, leukocytosis, and WBC fragments . Heinz bodies, Howell–Jolly bodies, Pappenheimer bodies, or basophilic stippling may also interfere with reticulocyte evaluation by hematology analyzers using flow cytometry .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other causes for discrepancies between automated and manual reticulocyte analyses include the presence of giant platelets, platelet clumps, abnormal WBC, leukocytosis, and WBC fragments . Heinz bodies, Howell–Jolly bodies, Pappenheimer bodies, or basophilic stippling may also interfere with reticulocyte evaluation by hematology analyzers using flow cytometry .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, none of these abnormalities were found in dogs with abnormal reticulocyte dot plots and large form babesiosis, and only parasitized RBCs could explain the abnormal profile. Previous studies have shown that in some leukemic human patients and in a leukemic dog, the reticulocyte count was erroneously increased, with an abnormal reticulocyte profile in which the reticulocyte region was completely separated from the RBC region, as observed in some leukemic dogs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A phenomenon called pseudoreticulocytosis is described to occur in samples with leukocytosis when analysed by flow-cytometry-based measures as is the case with the Advia 2120. 35,36 However, the animal did not show leukocytosis or large amounts of eosinophils in the peripheral blood and such interference with cell count is therefore improbable in the presented case. Furthermore, the blood results on day 3 and 6 might have been influenced by the blood transfusions and have to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 63%
“…The variation in reticulocyte count from day to day, for example, should have been rechecked. A phenomenon called pseudoreticulocytosis is described to occur in samples with leukocytosis when analysed by flow‐cytometry‐based measures as is the case with the Advia 2120 35,36 . However, the animal did not show leukocytosis or large amounts of eosinophils in the peripheral blood and such interference with cell count is therefore improbable in the presented case.…”
Section: Discussionmentioning
confidence: 66%
“…In oncology, for example, live and dead cell counting is typically performed to monitor the viability of cancer cells after different chemical [9] or radiobiological treatments [10]. Count accuracy can strongly influence the choice of treatment [11] and also lead to adjustments in the chemotherapeutic protocol [12] and in the drugs dosage administered to the patient [13].…”
Section: Introductionmentioning
confidence: 99%